SOCIAL REPORTING AS AN INDICATOR OF THE ENTERPRISE DEVELOPMENT - Maria Karpushenko (Сучасний стан наукових досліджень та технологій в промисловості, 2018)
Over the recent years, social activities have been a very significant index of the activity of domestic enterprises. These events do not indicate only the development of an enterprise but also suggests the opportunity to provide certain benefits to the society. But in Ukraine today there are no approved domestic standards which contain the structure of such reports and a list of issues that should be covered in them. This requires a thorough study of the theoretical and practical aspects of social reporting, the characteristics of foreign standards. The goal of the article is to study social responsibility, the aspects of social reporting, users, structure and indicators that can be included in it. The study deals with scientific works of foreign and domestic economists on the issues of social responsibility and accountability. The study is based on the combination of methods and approaches such as the dialectical method, the method of synthesis as well as the comparative and systemic ones. The following results were obtained: the issues of social responsibility of business and social reporting, the users of social reporting and their needs were investigated, international accounting practices were considered, namely the international standards of social reporting, such as Sunshine; AA1000; ISO 26000, SA8000 as well as the most famous and most commonly used GRI. The domestic practice of social reporting, problems and aspects domestic enterprises face were analyzed. On the basis of the analysis of international standards and the structure of social reporting of companies, the MLESQ indicator system is suggested, which can be applied for social reporting, taking into account the characteristics of the social activity of an enterprise. Conclusions. It is proved that solving the tasks of social reporting requires professional dialogue between social responsibility specialists, financial directors, accountants and auditors within the business structure itself.